Macrocyclic Effects in the Mesomorphic Properties of Liquid-Crystalline Pillar[5]- and Pillar[6]arenes - Nierengarten, Iwona; Guerra, Sebastiano; Holler, Michel; Karmazin-Brelot, Lydia; Barberá, Joaquín; Deschenaux, Robert; Nierengarten, Jean-François (My University, 2013)
Whereas the reaction of 1,4-bis(2-bromoethyloxy)benzene (4) with paraformaldehyde in the presence of BF3·Et2O afforded exclusively the cyclopentameric pillar[5]arene derivative (5), both cyclopenta- and cyclohexameric macrocycles 5 and 6 were obtained when the reaction of 4 with paraformaldehyde was performed at 45 °C in CHCl3 with FeCl3 as the catalyst. Treatment of compounds 4–6 with sodium azide provided the corresponding polyazides, to which a cyanobiphenyl building block was subsequently grafted to generate model compound 1, pillar[5]arene 2, and pillar[6]arene 3, bearing two, ten and twelve mesomorphic subunits, respectively. The liquid-crystalline and thermal properties of the compounds were investigated by polarized optical microscopy (POM), differential scanning calorimetry (DSC), and X-ray diffraction (XRD). Comparison of the liquid-crystalline properties of macrocycles 2 and 3 with those of 1 revealed the strong influence of the macrocyclic pillar[n]arene core on the mesomorphic properties. Whereas only a monotropic mesophase was observed for 1, a broad enantiotropic mesophase was evidenced for both pillar[n]arene derivatives.
Keywords: Nanostructures; Macrocycles; Liquid crystals; Structure elucidation; Click chemistry